INTEGRATED ALGORITHM FOR COMPILINGAND ASSESSMENT OF DIRECT ROUTES RESTRICTIONS IN FREE ROUTE AIRSPACE OF UKRAINE - Chynchenko, Yuriy; Kharchenko, Volodymyr (Proceedings of National Aviation University (archive), 2021)
The article describes the principles of acceptability assignment for direct routes restrictions in free route airspace of Ukraine for publication in Route Availability Document and further use by the Integrated Initial Flight Plan Processing System of Eurocontrol. The algorithms of correct generation of direct routes restrictions for the selected issues in a horizontal and vertical plane were proposed. As a main decision criteriafor these algorithms were chosen the shortest distance to the state boundary (in a horizontal plane) and space attitude (location) of aircraft (in avertical plane).